Innovative transparent and translucent materials on façades : non-visual effects of light - Costa, João Francisco Walter (2022)
Windows are responsible for important attributes related to the user’s well-being, such as the presence of daylight and view to the outside, with visual and non-visual effects. The circadian cycle can be defined as our biological clock, which can be stimulated with the light intensity and less intensely with the spectrum. In this context, innovative materials, such as electrochromic glazing and microstructured optical components can help maximize daylight in the built environment and at the same time can filter unwanted solar radiation, protecting users from glare. From the present studies it is still unclear how the employment of these materials on facades affects non-visual effects. Therefore, the aim of the study is to give an overview of the non- visual effects of these materials on users in non-residential buildings. The method consisted of a literature review and its systematization of documents, metrics and available methods to evaluate how the employment of the electrochromic glazing and microstructured components can affect non-visual effects. It was concluded that these two materials have the potential to balance visual comfort and at the same time provide daylight. Yet it is important to extend these studies, particularly to warmer climates.